Doctoral graduate profile: A proposal from documentary analysis and doctoral students’ expectations - Núñez´ Valdés, Karen Patricia; González Campos, José (IE Revista de Investigación Educativa de la REDIECH, 2019)
This article presents a discussion between the expectations of doctoral students related with the competences they should acquire after their doctoral training, the European regulations, specifically, the documents that come up from the Bologna Process and the Chilean regulations, defined through the guidelines developed by the National Accreditation Commission for postgraduate training. From this dialogue, it is proposed to develop a standard Graduate Profile for Doctoral programs in Education, through a quantitative methodology, based on content analysis. As a result, a standard Graduate Profile is presented, based on the New Zealand model, where the different competences that a Doctor of Education must acquire are contemplated, with it is intended to advance towards the homogenization of the Graduate Profiles of this university level and to contribute to the evaluation of existing Graduate Profiles.